Numerical Simulations of Fog Formation and Evolution in Alentejo Region - Policarpo, Carlos (2015)
The effect of fog on human life was recognized in the early ages of mankind but its impact has significantly increased during recent decades due to increasing air, marine, and road traffic. In fact, the financial and human losses related to fog and low visibility became comparable to the losses from other weather events, e.g., tornadoes or, in some situations, even hurricanes, mainly, because they occur more frequently. For example, in aviation a fog phenomenon often cause delays, diversions or cancellations that have various impacts on society, mainly economic impacts. As visibility is one of the most difficult weather variables to predict, its understanding becomes very important. The fog formation involves several processes, such as cloud physics, aerosols chemistry, radiation, turbulence, the large and small scale dynamics and surface conditions, including water bodies, topography, vegetation and soil type. High moisture, condensation nuclei and cooling process are the conditions for its formation. Often occurs in atmospheric stability situations during clear sky nights and with light to calm wind. It can be enhanced if air pollutants are present. Therefore, numerical simulations of fog events in Alentejo Region are presented, using capabilities of MESO -NH (Non-Hydrostatic Mesoscale Model) model. Surface observations of the Air Base No. 11 weather station in Beja were used in the model validation as well as Remote Sensing data from the satellite METEOSAT-10. Visual analysis of meteorological patterns observed by satellite and modeled with the Meso-NH provides a good approximation, and also there is a satisfactory correspondence between data obtained by meteorological observation at Air Base No. 11 and the analogous model point.